Pemanfaatan Minyak Goreng Bekas Menjadi Biodiesel di Desa Gedung Harapan Kec. Jatiagung - Rajiman; Sugito; Yulfriwini; Ikhsan Karim (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Energy needs are increasing, while the energy sources used so far have come from petroleum, natural gas and coal (fossil fuels) which are non-renewable and the amount always decreases from time to time. Energy sources derived from renewable fuels are a solution to this problem. One type of product from renewable energy sources derived from vegetable oil is biodiesel (methyl ester). Biodiesel is a monoalkyl ester of long chain fatty acids contained in vegetable oils or animal fats for use as diesel engine fuel. The implementation stage of this activity begins with the preparation of raw materials in the form of preparation of used cooking oil and filtering. The second stage is dissolving caustic soda (2-3 g) into methanol liquid (5:1 methanol water). The third stage is mixing the oil with a solution of methanol and caustic soda into a bottle and allowed to stand for 24 hours, this stage aims to separate the glycerol content in the oil. The fourth step is to separate the oil with solid glycerol and transfer it to an empty container to be mixed with warm water, this aims to remove excess methanol liquid in the oil, let stand for 24 hours. The last step is to separate the oil from the mixing water. From the results of this experiment, a ready-to-use biodiesel liquid was obtained.